PENGARUH PENERAPAN STRATEGI PEMBELAJARAN AKTIF TIPE PREDICTION GUIDE TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VIII MTsN LUBUK BUAYA PADANG - Frestian, Anike; Febriana, Rina; Lovia, Lita (STKIP PGRI Sumbar, 2014)
ABSTRACTThis research is motivated by less students are responsible for completing the tasks assigned teacher and students are less motivated to follow the learning of mathematics as well as students understanding of mathematical conceptual are still low. This research was aimed at revealing whether the use of Prediction Guide strategies could give a better effect on the studentsâ understanding on mathematics conceptual than the conventional one in class VII MTsN Lubuk Buaya Padang.This was an experimental research which used random research design toward the subject. The instrument used in this research is a test in studentsâ understanding on mathematics conceptual. Based on the result of data analysis, it was revealed that the sample was distributed normally and had homogeny variant. Hypothesis test results obtained t=2,09 was bigger than Â indicating that the hypothesis was accepted. So, it was concluded that the application of Prediction Guide strategies could improve the studentsâ understanding on mathematics conceptual, and better than the conventional one.